2017
DOI: 10.1108/jarhe-07-2015-0060
|View full text |Cite
|
Sign up to set email alerts
|

Using mobile learning and social media to enhance learner feedback

Abstract: Purpose The purpose of this paper is to investigate an area of growing importance that is widely recognised in the literature relating to the issue of how to improve ways that assessments and feedback are provided to students within higher education. This paper reports on a study that aimed to explore the views of both educators (n=70) and students (n=540) on feedback and feed-forward at a UK university. The study also investigated their experience and attitudes to social media applications as a means of enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Following the phases of GMDR, the study started with a literature review, followed by initial fact-finding studies involving both lecturers and students. The purpose of the fact-finding studies (survey and follow-up interviews) was to seek participants’ views in relation to assessment feedback and mobile learning (Bikanga Ada et al 2017). The first draft of the framework emerged from the literature review and was updated after the initial (explorative) fact-finding studies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the phases of GMDR, the study started with a literature review, followed by initial fact-finding studies involving both lecturers and students. The purpose of the fact-finding studies (survey and follow-up interviews) was to seek participants’ views in relation to assessment feedback and mobile learning (Bikanga Ada et al 2017). The first draft of the framework emerged from the literature review and was updated after the initial (explorative) fact-finding studies.…”
Section: Methodsmentioning
confidence: 99%
“…Evans (2013) reviewed 460 articles on assessment feedback from 2000 to 2012 and found that most of the problems arise due to the fact that the student population has increased in higher education, due to which the unit of resource is being stretched and there is growing pressure on academic staff regarding traditional assessment. Bikanga Ada et al (2017) investigated students’ ( n = 540) and educators’ ( n = 70) perception of assessment and feedback, and identified several issues that have also been highlighted in the literature. These issues include lack of student engagement and motivation with assessment feedback; educators being unhappy because, despite all their effort, students do not collect their assessment feedback; and high student numbers affecting the capacity to provide timely and personalised feedback (Bikanga Ada et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fuchs and Woessmann (2004) analyzed the international data from the Program for International Student Assessment (PISA) and revealed that there is a significantly positive correlation between the availability of ICT and students' performance. When individuals demonstrate a positive attitude to and possess great interest in digital learning and social media applications, their individual learning needs and experiences are enhanced, which in turn assist them to achieve better learning outcomes (Ada et al, 2017;Baxter & Connolly, 2014). He et al (2019) examined the effects of a flipped classroom, in which students work in groups and construct knowledge with the help of their teacher and peers using student-centered instruction.…”
Section: Information and Communication Technology (Ict)mentioning
confidence: 99%
“…It has also explored seamless learning by going outside the confinement on time and place [57]. Moreover, their students' positive attitudes towards mobile learning has greatly affect their motivation and interest towards greater learning [58]. With mobile learning technology, mobility is a prime platform towards highlighting technology utilization in learning [59].…”
Section: Irche 2017mentioning
confidence: 99%